Performance Analysis of FBMC O-QAM System Using Varied Modulation Level - Prieska Marina; Anggun Fitrian Isnawati; Mas Aly Afandi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
Communication channels that are affected by various disturbances will cause a high Bit Error Rate (BER). To maximize the performance of the channel in the future, Filter Bank Multicarrier (FBMC) technique is used as a renewal of Orthogonal Frequency Division Multiplexing (OFDM). FBMC has better spectrum efficiency properties due to the nature of orthogonality which only divides bandwidth for sub-channels. The purpose of the research was to knowing the performance of FBMC Offset QAM (FBMC O-QAM) which has a variation of modulation levels of 4-QAM, 16-QAM, and 64-QAM. The Zero Forcing (ZF) method is used to detect the original signal sent by the transmitting antenna. System performance in this study was measured by parameter Bit Error Rate (BER) and channel capacity. The results showed that the FBMC O-QAM system with ZF has decreased BER value on each modulation. At the time of modulation 4 QAM has a BER value of 0.0008945 with an SNR value of 20 dB. Modulation 16 QAM also experienced the same thing when the SNR value of 20 dB has BER value of 0.001856, and at modulation 64 QAM has BER value of 0.01766 at a SNR of 20 dB. Besides decreasing the BER parameters, the FBMC O-QAM ZF system has own characterize in channel capacity. For the 4-QAM has 4.808 b/s/Hz, 16-QAM has 4.627 b/s/Hz, and 64-QAM has 3.903 b/s/Hz at SNR 20 dB. It conclude that 4-QAM has a best channel capacity enhancement. The value of channel capacity generated based on simulations using Zero Forcing shows an increase in value along with an increase in SNR, but has a smaller value compared to channel capacity in theory.